Blood Mixing Upregulates Platelet Membrane-Bound CD40 Ligand Expression In Vitro Independent of Abo Compatibility. Issue 3 (September 2018) - Huang, Go-Shine; Hu, Mei-Hua; Lin, Tso-Chou; Lin, Yi-Chang; Tsai, Yi-Ting; Lin, Chih-Yuan; Ke, Hung-Yen; Zheng, Xu-Zhi; Tsai, Chien-Sung
Abstract : ABSTRACT: Platelets play a central role in the inflammation response via CD40 ligand (CD40L) expression, which may lead to transfusion reactions. The precise role of platelet CD40L-mediated inflammation in transfusion reactions is unclear. Therefore, we assessed the effects of in vitro blood mixing on platelet CD40L expression. In addition, we examined the effect of ABO compatibility on CD40L expression. Donor-packed red blood cells were acquired from a blood bank, and recipient blood was obtained from patients undergoing cardiac surgery and prepared as washed platelets. Donor blood was mixed with suspended, washed recipient platelets to obtain a final mixing ratio of 1%, 5%, or 10% (vol/vol). The blood mixtures were divided into three groups: group M, cross-matched blood-type mixing (n = 20); group S, ABO type-specific uncross-matched blood (n = 20); and group I, ABO incompatibility (not ABO type-specific blood and not process cross-matched) mixing (n = 20). The blood mixtures were used to detect platelet membrane-bound CD40L expression by flow cytometry. Blood mixing resulted in an increase in CD40L expression in group M ( P  < 0.001), group S ( P  < 0.001), and group I ( P  < 0.001). CD40L expression after blood mixing potentially led to a transfusion reaction in each of the groups. There were no differences in CD40L expression among the three groups ( P  = 0.988) correlated with ABO compatibility or incompatibility. This indicates that the reactions between red blood cell surface antigens and plasma antibodies do not play a role in the induction of CD40L expression.